Shocking velocity - Srinivas, Srikanth (Emerald Publishing Limited : Information Age Pub. Inc., 2005)
Srikanth Srinivas has helped companies like Del Monte, Disney, Dole, FritoLay, Microsoft and Target Rapidly Achieve More With Less - More Revenues, Margins and Cash Flow, With Less Costs, Assets and Inventory. In "Shocking Velocity!" he will show you how you can create similar results for your organization. It is like having the best consultants from McKinsey, Accenture and IBM guiding you towards success - at a fraction of the cost, and with your own people learning and applying the best methodologies for success.The central theme of the book is "Focused Changes to Critical Variables Create Superior Value". Small, focused changes to critical variables result in a big impact on bottom line results. The book describes what those critical variables are, and how to make focused changes to realize benefits systematically with minimum risk. It takes you step-bystep through everything you need to understand, change and strike the right balance between the critical variables: Variety, Velocity, Visibility and Variability; and how making focused changes to these variables will result in superior Value.It doesn't stop there. It makes it all actionable by describing in detail an approach that maximizes benefits while minimizing risk: Diagnose & Baseline, Divide & Prioritize, Design & Align, Deliver & Learn. Making these focused changes will help you rapidly achieve more with less - more revenues, margins and cash flow with less costs, inventory and assets.It is filled with illustrations that distill the essence of complex ideas, and makes them actionable in your unique context. There are stories, quotes, case studies and examples - all meant to keep your attention, drive home the point and inspire you to take actions."Shocking Velocity!" is a practical book that explains breakthrough concepts, gives examples of how these innovative concepts can be applied, what performance measures can be used to monitor progress, and how to create a culture of continuous improvement. You will also find a detailed explanation of the approach you should take to make the changes entirely self-funding.It is written for these tough economic times. It doesn't stop at explaining concepts. It brings them to life and helps you apply the ideas in your unique context; applying these ideas can make all the difference between struggling for survival and growing stronger through the tough times by creating superior value. The chart to the left illustrates the kind of benefits you can create for your organization by applying the ideas in the book. It is no "get-rich-quick" scheme, but there are ingenious ideas in the book to get you results fast; and more importantly, each little step will be aligned towards helping you create significant results over time. This will result in a culture of continuous improvement that will help you sustain operational excellence, and stay competitive and agile.Best of all, it is short, precise and to the point. You will finish reading it in less than 2 hours. Happy Reading! More importantly, Happy Implementing!